Approximation by invertible functions of H^∞ - Nicolau, Artur; Suárez, Daniel (MATHEMATICA SCANDINAVICA, 2006)
We provide an analytic proof that if H^∞ is the algebra of bounded analytic functions on the unit disk, A is a Banach algebra and f: H^∞ → A is a Banach algebras morphism with dense image, then f((H^∞)^-1) is dense in A^-1.